Design and Fabrication of a Three-Dimensional In Vitro System for Modeling Vascular Stenosis. (17th July 2017) - Jones, Rebecca S.; Chang, Pin H.; Perahia, Tzlil; Harmon, Katrina A.; Junor, Lorain; Yost, Michael J.; Fan, Daping; Eberth, John F.; Goodwin, Richard L.
Abstract: Vascular stenosis, the abnormal narrowing of blood vessels, arises from defective developmental processes or atherosclerosis-related adult pathologies. Stenosis triggers a series of adaptive cellular responses that induces adverse remodeling, which can progress to partial or complete vessel occlusion with numerous fatal outcomes. Despite its severity, the cellular interactions and biophysical cues that regulate this pathological progression are poorly understood. Here, we report the design and fabrication of a three-dimensional (3D) in vitro system to model vascular stenosis so that specific cellular interactions and responses to hemodynamic stimuli can be investigated. Tubular cellularized constructs (cytotubes) were produced, using a collagen casting system, to generate a stenotic arterial model. Fabrication methods were developed to create cytotubes containing co-cultured vascular cells, where cell viability, distribution, morphology, and contraction were examined. Fibroblasts, bone marrow primary cells, smooth muscle cells (SMCs), and endothelial cells (ECs) remained viable during culture and developed location- and time-dependent morphologies. We found cytotube contraction to depend on cellular composition, where SMC-EC co-cultures adopted intermediate contractile phenotypes between SMC- and EC-only cytotubes. Our fabrication approach and the resulting artery model can serve as an in vitro 3D culture system to investigate vascular pathogenesis and promote the tissue engineering field.